Temporal Dynamics of Phytoplankton in Retention Pond as a Water Source for Striped Catfish (Pangasianodon hypophthalmus) Farming - Dhuha, Orbita Roiyan; Hastuti, Yuni Puji; Malau, Albert Gamot (Buletin Jalanidhitah Sarva Jivitam, 2024)
This comprehensive study investigates the temporal dynamics and ecological aspects of phytoplankton communities in water reservoirs utilized for Pangasius cultivation. Over a six-week observation period, 25 phytoplankton species, including Bacillariophyceae, Chlorophyceae, Cyanophyceae, Euglenophyceae, and Cryptophyceae, were identified. Chlorophyceae displayed the highest species richness, emphasizing the dominance of this group, particularly Chlorella, which remained stable throughout weekly observations. Other taxa, such as Euglenophyceae, exhibited delayed increases in density. The study revealed two crucial groups in the water reservoir: the first, composed of Actinastrum sp., Closterium sp., Staurastrum sp. (Chlorophyceae), Navicula sp., Pleurosigma sp., Schroedaria sp., Surirella sp. (Bacillariophyceae), and the second, more diverse group consisting of Nitzschia sp. (Bacillariophyceae), Cryptomonas sp. (Cryptophyceae), Trachelomonas sp. (Euglenophyceae), Anabaena sp., Merismopedia sp., Phormidium sp. (Cyanophyceae), Ankistrodesmus sp., Chlorella sp., and Crucigenia sp. (Chlorophyceae). Chlorella was consistently present which was observed to interact with various species, fostering a balanced environment for growth and reproduction within its family and across others based on network analysis. Contradictory dynamics emerge in the initial weeks, where the highest species richness (N = 19 species) coincides with a high dominance index (1/D = 0.54). Conversely, the peak diversity index (H’ = 2.04) occurs during the second observation, aligning with a comparable evenness index (J = 0.89). The saprobic index indicates a shift in pollution levels from β-mesosaprobic to α/β-mesosaprobic between the initial and final weeks of observation. Simultaneously, trophic-saprobic index alterations signify an environmental quality transition from polysaprobic to oligosaprobic. This presents contradictory trends, where, based on species richness, the environment is ecologically classified as polluted. However, considering the contribution of non-indicator groups in the formula, the pond conditions shift towards nutrient impoverishment, suggesting potential suitability for aquaculture practices.